Instagram in Learning Spoken German - Nurming Saleh; Mantasiah R; Irmayanti Irmayanti (Interference: Journal of Language, Literature, and Linguistics, 2022)
Abstract. The aim of this research was to obtain data and information on the effectiveness of Instagram in German speaking for students class X SMAN 1 Maros. This research was Quasi Experimental with the form Non Equivalent Control Group Design. Sample of this research was the students class X SMAN 1 Maros, which consisted of 68 students and class X MIPA 5 as experimental class and class X MIPA 6 as control class and were selected randomly. Instrument in this research was a test of students speaking skills. Data were collected through the results of speaking skills test and data were analyzed using T-test. The results of data analysis show that Tcount (4,046)  Ttable (1,998) with a significance level of 0,05. This means that Instagram is effective in the German speaking of students class X SMAN 1 Maros.  Keywords : Instagram, Speaking, German